Students’ Multimedia-Assisted Scientific Inquiry Ability on The Material of Reproductive Cells (Jurnal Pendidikan IPA Indonesia, 2017)
This study aims to: (1) explore students’ learning achievement based on scientific inquiry learning on the materials of reproductive material cells reflected on pre-test and post-test; (2) obtain the achievements of scientific inquiry activity based on the different time of problem distribution; and, (3) analyze students' ability in scientific inquiry activities based on the indicators of scientific inquiry in the different time of problem distribution. The design was research development. The participants were two classes of PGMI. The research data were pretest and posttest obtained from close-ended test and scientific inquiry activities obtained from student worksheet. Research shows that learning outcomes of students in each class increases, though there is no significant difference in the increase indicated in the learning outcomes between the two classes. The technique of distributing students’ work in different time influence the students' scientific inquiry activity. Communication is a dominant indicator of the successful scientific inquiry activities in both classes. Using the data and creating an image are other indicators affecting the scientific activity.